2021
DOI: 10.1002/tee.23487
|View full text |Cite
|
Sign up to set email alerts
|

An Energy Management Strategy Based on Fuzzy Logic for Hybrid Energy Storage System in Electric Vehicles

Abstract: To solve the problem of battery capacity degradation caused by high current magnitudes and frequent current variations in electric vehicles (EVs), a hybrid energy storage system (HESS) incorporating high energy density storage (battery) and high power density storage (ultracapacitor) is proposed. The HESS contains a multi-port DC-DC converter, which controls the energy flow among the battery pack, the ultracapacitor (UC) pack, and the port of output. Considering the state of charge (SOC) of UC, the speed, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Some studies have used scenario clustering methods to improve computational efficiency while preserving the characteristics of PV-Load [16], [17]. Scenario generation methods such as k-means clustering algorithm [18], fuzzy C-means clustering algorithm [19], and hierarchical clustering [20] have been widely applied. However, these methods measure similarity using Euclidean distance when dealing with high-dimensional time series data, and the clustering scenarios need to be determined in advance, resulting in lower clustering quality.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have used scenario clustering methods to improve computational efficiency while preserving the characteristics of PV-Load [16], [17]. Scenario generation methods such as k-means clustering algorithm [18], fuzzy C-means clustering algorithm [19], and hierarchical clustering [20] have been widely applied. However, these methods measure similarity using Euclidean distance when dealing with high-dimensional time series data, and the clustering scenarios need to be determined in advance, resulting in lower clustering quality.…”
Section: Introductionmentioning
confidence: 99%
“…The EMS can be divided into rule‐based control, model‐based optimization, and learning‐based methods. The rule‐based control strategy controls the power demand of each power source in different driving modes [3–5]. This approach has better real‐time performance but does not involve direct optimal control due to usually using heuristics or engineering intuition with rules.…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al [ 25 ] have suggested fuzzy logic control (FLC) for the EMS of HESS on EV. The degradation of the battery issues was solved by the utilization of battery and ultracapacitor (UC).…”
Section: Introductionmentioning
confidence: 99%